The relationship between anxiety about prostate cancer among patients with biochemical cancer recurrence and the use of complementary and alternative medicines, diet, and exercise. Issue 2 (1st July 2017) - Lee, Richard T.; Hemmerich, Joshua A.; Kwon, Nancy; Bylow, Kathryn; Stadler, Walter M.; Mohile, Supriya G.; Dale, William
Abstract : Objective: We aimed to explore associations between anxiety and specific health behaviors such as complementary and alternative medicine (CAM), diet, and exercise among prostate cancer patients. Methods: PCa patients enrolled in a prospective cohort study of men with biochemical cancer recurrence were surveyed about use of CAM, diet, and exercise. Anxiety was measured with the Memorial Anxiety Scale for Prostate Cancer (MAX-PC) and the anxiety subscale of the Hospital Anxiety and Depression Scale. Results: Nearly 70% (44 of 67) of the original cohort of patients completed the supplementary CAM survey. The mean age was 68 years. Eighty percent of respondents reported engaging in a relevant health behavior, and 64% reported doing so in direct response to their PCa diagnosis. Overall, the most prevalent specific behaviors were exercising (56%), making dietary changes (50%), taking calcium supplements (41%), and taking vitamin D supplements (39%). Elevated baseline PCa-specific anxiety (MAX-PC score >16) after biochemical cancer recurrence was associated with use of any CAM ( P =0.01), use of herbs/supplements ( P =0.01), and dietary changes ( P =0.04). Conclusion: PCa patients commonly use CAM, dietary changes, and exercise in response to their diagnosis, and these changes are associated with elevated general and PCa-specific anxiety.